Pengaruh Kompetensi Dan Karakteristik Individu Terhadap Kinerja Guru Di SMPN 6 Bangkalan - Enni Triastutik; Nugroho Mardi W; Chamariyah Chamariyah (Journal of Management and Creative Business, 2024)
The Influence of Competence and Individual Characteristics on Teacher Performance at SMP Negeri 6 Bangkalan. Wijaya Putra University Postgraduate Program in Surabaya.This type of research uses explanatory research, the research approach uses a quantitative approach. The research sample was 45 teachers. The aims of this study were 1) to test and analyze whether competency directly influences the performance of teachers at SMP Negeri 6 Bangkalan. 2) To test and analyze whether the characteristics directly influence the performance of SMP Negeri 6 Bangkalan teachers.The results showed that: 1) Competence had a significant positive effect on teacher performance at SMP Negeri 6 Bangkalan with an original sample value of 0.349. 2) Individual characteristics have a significant positive effect on teacher performance at SMP Negeri 6 Bangkalan with an original sample value of 0.267.